Ta có
\(x=\frac{1}{2}\sqrt{\frac{\sqrt{2}-1}{\sqrt{2}+1}}=\frac{1}{2}\sqrt{\frac{\left(\sqrt{2}-1\right)^2}{\left(\sqrt{2}+1\right)\left(\sqrt{2}-1\right)}}\)
\(=\frac{1}{2}.\frac{\left(\sqrt{2}-1\right)}{1}=\frac{\sqrt{2}-1}{2}\)
Ta lại có
\(x+1=\frac{\sqrt{2}-1}{2}+1=\frac{\sqrt{2}-1+2}{2}=\frac{\sqrt{2}+1}{2}\)
\(\Rightarrow x\left(x+1\right)=\frac{\sqrt{2}-1}{2}.\frac{\sqrt{2}+1}{2}=\frac{1}{4}\)
Ta lại có
\(4x^4+4x^3-5x^2+5x-2=4x^3\left(x+1\right)-5x^2+5x-2\)
\(=x^2-5x^2+5x-2=-4x^2\left(x+1\right)+9x-2\)
\(=-1+9x-2=-3+\frac{\sqrt{2}-1}{2}=\frac{\sqrt{2}-7}{2}\)
Giải tới đây thì mình nghĩ là bạn sai đề rồi. Bạn xem lại đề nhé
ờ sai đề thật , mk cũng làm đc rùi nhưng vẫn cảm ơn nha